Hubungan Faktor Keturunan dengan Kanker Payudara: Studi Literatur - Heni Anggraini (Pelantar Press, 2025)
Cancer is a non-communicable disease and a significant public health issue. Among women, breast cancer is the most common type of cancer and is the second leading cause of cancer-related deaths, following lung cancer. Breast cancer can be sporadic, familial, or hereditary. In Indonesia, breast cancer has the highest incidence rate at 42.1 per 100,000 population. The purpose of this writing is to identify the risk factors for breast cancer. The method used is a literature review, involving searches for keywords such as cancer, breast, malignancy, breast cancer, and mammary in Google Scholar and PubMed. A review of national and international journals summarizes the discussed topics and compares the results presented. Several studies have identified the following risk factors for breast cancer: family history of breast cancer, age at menarche, age at first childbirth, nulliparous parity, history of breastfeeding, obesity, and physical activity.